Entrepreneurship Education in Finland - Heinonen Jarna; Ilonen Sanna (Springer Publishing Company, 2025)
This Chapter aims at presenting the state-of-the-art of entrepreneurship education (EE) in Finland through the lenses applied in this volume. We first provide ground for the chapter by describing the context for EE in Finland. We continue by discussing the internal development of EE in the individual HEIs based on the information provided in their websites in the Fall 2021.Then we describe the supporting systems of EE in HEIs and the characteristics of EE by highlighting an example of an Entrepreneurial University. We conclude with alternative futures toward higher quality of EE.
Comparative Entrepreneurship Education